Quantitative damping reshaping method based on equivalent RLC circuits using an active damper. Issue 1 (26th July 2022) - Li, Fei; Feng, Qiang; Wang, Yichao; Wang, Hanyu; Ma, Mingyao; Zhang, Xing
Abstract: Large scale power electronic converters in renewable energy power system (REPS) constitute a complex multi‐scale high‐order non‐linear network. Harmonic amplitude amplification of specific frequency (e.g. harmonic resonance) often occurs in stable REPS, threatening the normal operation of the system. The impedance reshaping methods based on the stability margin cannot quantitatively assess the risk of harmonic resonance, so that the reshaped system damping may be in a state of under‐ or over‐damped. This paper proposes a harmonic damping concise estimation (HDCE) method based on the one port equivalent RLC impedance model, which quantitatively describes the magnitude of harmonic damping of the system. Aiming at the harmonic damping of the system in an ideal power network, a method of quantitative reshaping of system damping based on HDCE using active damper is proposed, which ensures that the reshaped system is neither under‐damped nor over‐damped. The harmonic resonance is suppressed effectively while the current stress of the active damper is kept as small as possible. Simulation and experimental results verify the correctness of these analytical and quantitative damping reshaping methods.